The Influence of Market Orientation, Entrepreneurial Orientation, and Product Innovation on Marketing Performance by Predominance Competitive (Journal of Economic Education, 2022)
The aim of this study is to find out the marketing performance of a small industry known as IKM on fish processing influenced by market orientation, entrepreneurial orientation, and product innovation by predominance competitive as the mediating variable. It is a quantitative research study. The data was collected by questionnaire and analyzed by path analysis. The population was the businessmen of fish processing IKM in Tegal consisted of unit salting unit, fillet, tender, crackers, shrimp paste, pindang and grilled. It was around 239 units of IKM, with 70 businessmen as the sample. Results of the study shows that this research model is appropriate for this topic. Market orientation has a positive and significant influence on predominance competitive for 17.81%, entrepreneurial orientation has a positive and significant effect on predominance competitive for 13.25%, product innovation has a positive and significant effect on predominance competitive for 4.45%, market orientation has a positive and significant effect on marketing performance by predominance competitive for 40.22% in total, entrepreneurial orientation has a positive and significant effect on marketing performance by predominance competitive for 47.81% in total, product inovation has a positive and significant effect on marketing performance by predominance competitive for 19.24% in total, predominance competitive has a positive and significant effect on marketing performance for 50.30%.